Evaluación del rendimiento del cultivo maíz (Zea mays) con dos niveles de zeolita y dos niveles de urea en la finca paraíso escondido, cantón Pangua, provincia de Cotopaxi, año 2013 - Quishpe Punina, Rosa Zoila (2015)
In this research work, it was found as the main problem the infertility and poor performance of the soil, the general objective was the following: To evaluate the performance of corn (Zea mays) using two levels of zeolite and two levels of urea, to determine the response of this crop applying two levels of zeolite and two levels of urea, to stablish a proper fertilization on this crop, and to analyze the production yield in maize according to the application of these products as urea and zeolite, the design that was used was a randomized complete block design (RCBD) with factorial arrangement, with three levels of zeolite and three levels of urea and three repetitions, with four plants for treatment were taken....